Analysis of Job Satisfaction of Health Workers at Bahteramas Hospital - Sumarti, Sumarti; Muharni; Syamsiah; Candra; Tosepu, Ramadhan; Effendy, Devi Savitri; Susanty, Sri (Universitas Mandala Waluya, 2023)
Employee job satisfaction is characterized by a low proportion leaving the organization and low employee absenteeism. The survey on the job satisfaction of health workers at the Bahteramas Hospital BLUD showed 46% were satisfied at work such as conducive working conditions, and incentives received according to workload while 54% were dissatisfied because there was no compensation related to time of attendance. The purpose of this study was to determine the relationship between working conditions, incentives, work performance and satisfaction of health workers. This research is a quantitative (Observational) research design cross-sectional study. The research was conducted from 1 to 20 February 2023 in the inpatient rooms of Bahteramas Hospital with 139 from 213 health workers using the Cluster Random Sampling technique. Data collection used a questionnaire and carried out a chi-square test and a closeness test. The results of the study found that more respondents with supportive working conditions were satisfied (p=0.006, j=0.233). Respondents with appropriate incentives were more satisfied with their job satisfaction (p=0.000, j=0.302). Furthermore, respondents with appropriate organizational policies were more satisfied with their job satisfaction, (p=0.005, j=0.237). The conclusion is that there is a moderate relationship between working conditions, incentives and achievement with health worker satisfaction in the BLUD Inpatient Room of Bahteramas Hospital.